IMPACT OF DAIRY MANAGEMENT PRACTICES ADOPTED BY WOMEN DAIRY FARMERS ON QUALITY OF MILK AT SOCIETY LEVEL - K. VENKATARAMANA, SURESH RATHOD and (The Journal of Research, PJTSAU, 2017)
The study was conducted to assess the impact of dairy management practices on the quality of milk at production levels (societies) in the Karimnagar district of Telangana state. A total of 2850 women dairy  farmers were interviewed for the questionnaire prepared. As per the studies the farm women from member and non member group not following the ideal management practices such as housing management (57.35&88.0%), cleaning of animal shed/shelter before milking  (34.50&38.89%), washing of animals before milking  (82.25&93.80%), washing of milkers hand before milking (43.30&33.96%),washing of udder at the time of milking(20.60&34.45%),wiping of udder with clean dry cloth before milking, dipping of teats in disinfectant solution (99%),cleaning anddrying of utensils (30.0&22.56%) and 62&81.50% of the respondent do not have the knowledge about mastitis, hence the management practices showed clear impact on quality of milk. The time taken for reduction of methylene blue was 3.98 &5.13 hrs. standard plate count and e.coli 32.64 ±1.55, 36.52± 5.94,33.44±1.47&,35.58± 0.18 respectively in member and nonmember groups which was below in compared with BIS standards and the over all quality is graded as fair